Association between surveillance imaging and survival outcomes in small bowel neuroendocrine tumors. Issue 4 (19th December 2022) - Watanabe, Akie; Mckendry, Geoffrey; Yip, Lily; Loree, Jonathan M.; Stuart, Heather C.
Abstract: Background: Surveillance guidelines following the resection of small bowel neuroendocrine tumors (SB‐NETs) are inconsistent. We evaluated the impact of surveillance imaging on SB‐NET recurrence and overall survival (OS). Methods: Patients with completely resected SB‐NETs referred to a provincial cancer center (2004–2015) were reviewed. Associations between imaging frequency, recurrence, post‐recurrence treatment, and OS were determined using univariate and Cox‐regression analyses. Results: Among 195 completely resected SB‐NET patients, 31% were ≥70 years, 43% were female, and 80% had grade 1 disease. Imaging frequency was predictive of recurrence (hazard ratio 2.52, 95% confidence interval 1.84–3.46, p  < 0.001). 72% underwent interventions for recurrent disease. Patients who were treated for the recurrent disease had comparable OS to those who did not recur (median 152 vs. 164 months; p  = 0.25). Imaging frequency was not associated with OS in those with treated recurrent disease ( p  = 0.65). Patients who recurred underwent more computerized tomography (CT) scans than those who did not recur (CT: 1.47 ± 0.89 vs. 1.02 ± 0.81 scans/year, p  < 0.001). Detection of disease recurrence was 5%–7% per year during the first 6 years of surveillance and peaked at 17% in Year 9. Conclusion: Less frequent imaging over a longer duration should be emphasized to capture clinically relevant recurrences that can be treated to improve OS.